The Influences of Sports Activities on Developing Purpose of College Students: Sports and Developing purpose of students - Dil Faraz Khan; S R Ghazi; Gulap Shehzad (Indonesia Approach Education, 2021)
The aim of this study was to investigate the influences of college sports activities on developing purpose of college students. The main objectives of this study is to identify the influences of college sports activities on developing purpose of college students and to compare the influences of individual and team sports activities on developing purpose of college student. The population of the study consisted of all students N= 749 participating in sports activities at college level in Bannu Division, while sample of the study consisted of students n= 150 at college level in Bannu Division. Influences of sports activities on developing purpose of college students were measured by self-developed questionnaires. SPSS-26 was used for data analysis. Multiple regressions was used to measure the influences of sports activities on developing purpose of college student, t-tests were used to identify significant differences between the influences of individual and team games on developing purpose of college student. This study showed that students develop their purpose of life in college and sports activities provide a dynamic environment in this regard. Statistically significant evidence is found from the data that students developed an academics purpose along with life purpose during college sports activities more significantly.